Influenza related pneumonia in children under five years old in Indonesia : An analysis of the risk factors - Ira Wignjadiputro; Ni Ketut Susilarini; Vivi Setiawaty; Renti Mahkota (Riset Informasi Kesehatan, 2018)
Abstract Background: Pneumonia is more commonly among children under five years old and caused by several risk factors. Pneumonia causes 1.9 – 2.2 million children death worldwide every year, in which 1.3 million (81%) generally occurs in first 2 years of life. Seventy two percent of pneumonia occurs in children under five years old in 15 countries. Indonesia was the 7th highest in the world. The prevalence of pneumonia in Indonesia was 18.5/1000 population and only 1.6/1000 received treatment. This study aim to elaborate the risk factors of the influenza related pneumonia in children under five years old. Method: The pneumonia control program in Ministry of Health focuses on early detection and treatment for bacterial pneumonia in community. Severe acute respiratory infection (SARI) can develop fatal pneumonia. We collected data from the pneumonia surveillance database in the Acute Respiratory Infection subdirectorate. Results: Influenza related pneumonia was 13% of acute lower respiratory infection in pediatric. The number of children under five years old death estimation was 28,000-115,000 and 99% happened in developing countries. The aim of this review is to understand influenza related pneumonia in Indonesia and global. Summary: In Indonesia, proportion of influenza from SARI surveillance was 12% and mainly in children under five years old (36%). Pneumonia was 18% of SARI cases with positive influenza. The effect of Influenza become pneumonia remain unclear.